Henoch-Schönlein Purpura, a Rare Disease in Pregnancy (Bangladesh Journal of Obstetrics & Gynaecology, 2010)
Introduction: Henoch-Schönlein purpura is an IgA-mediated small vessel vasculitis involving mainly skin, gastrointestinal system and kidneys. It is predominantly a disease of young children. Most common symptoms are rash (95-100%), sometimes necrotizing involving specially the legs, subcutaneous oedema (20-50%), abdominal pain and vomiting(85%), bloody stool and joint pain (60-80%) involving mainly the knees and ankles. Diagnosis is clinical and not based on laboratory evaluation. Its occurrence during pregnancy is exceptional. Materials & Methods: On literature search, till date only 17-18 cases of Henoch-Schönlein purpura in pregnancy were found. Case: Here we present a case report on this rare disease in pregnancy. A 39 year old lady, para 1+ 8 abortions, diagnosed as Henoch-Schönlein purpura at 24 weeks of gestation, treated with steroids and was cured almost completely. She was readmitted at 37 weeks of gestation with few purpuric rashes. Elective caesarean section was planned and a healthy male baby was delivered. But sub-total hysterectomy was needed for intractable bleeding from placental bed. Her post operative period was uneventful. Conclusion: Very few information we got on literature search on Henoch-Schönlein purpura in pregnancy. Corticosteroids and plasmapheresis have been practiced as treatment during pregnancy. If kidneys are unaffected, obstetrical prognosis is good. Key Words- Henoch-Schönlein Purpura; Pregnancy DOI: 10.3329/bjog.v23i2.4964 Bangladesh J Obstet Gynaecol, 2008; Vol. 23(2) : 73-77